(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
3D Printed (3DP) medical parts are continuing to be adopted for a variety of uses. Part quality is a continuing concern, with one aspect being cleanliness and the ability to be effectively cleaned. Porosity is a property that makes cleaning more difficult. A method of using pycnometry is described to measure porosity in complete 3DP parts. Pycnometry uses changes in volume and pressure to calculate the volume of a sample. The system is able to identify small variations in sample volume, and could be used to compare the actual part volume with the expected volume.